Do Leaders’ Emotional Labor Strategies Influence the Leaders’ Emotional Exhaustion? Moderating Role of Emotional Intelligence: Longitudinal Study on NGOs - Nisar, Qasim Ali; Imran, Asma; Othman, Noraini; Mustafa Kamil, Bidayatul Akmal; Marchalina, Leonis (American Scientific Publishers, 2017)
The purpose of this study is to examine the impact of leaders’ emotional labor strategies on leaders’ emotional exhaustion by considering the moderating role of emotional intelligence.Study is longitudinal, descriptive and quantitative in nature.By following emotional labor theory, theoretical framework has been testified by obtaining data from 400 leaders of 250 selected non-government organizations from all over the country.As study is longitudinal in nature therefore, data have been collected two times from same respondents by applying simple random sampling technique.By using the structural equation modeling technique, results divulged that leaders’ emotional labor strategies significantly associated with their emotional exhaustion. Specifically surface acting positively related to leaders’ emotional exhaustion while deep acting and display of genuine emotions negatively and significantly associated with leaders’ emotional exhaustion.Moderated hierarchical regression analysis proved that emotional intelligence significantly moderate the relationship between emotional labor strategies (surface acting, deep acting, display of genuine emotions) and leaders’ emotional exhaustion.Therefore leaders with high level of emotional intelligence can moderate their level of emotional exhaustion while performing emotional labor strategies.This study provides insight understanding and guidelines that how leaders can adopt different emotional labor strategies to tackle their emotional exhaustion level and to play their role in effective manners in non-government organizations.